Taiwan and China in a global value chain: the case of the electronics industry - Lee, Chun-Yi
This chapter aims to examine how Taiwan impacted upon China through the technology flow from Taiwan to China, and how Taiwan played a part in linking China’s manufacturing with the United States. Theoretically this chapter challenges the Global Value Chain (GVC) theory in that it overlooks the possibility that first-league countries may not be willing to share all the knowledge insights. This chapter also investigates the role of Taiwan in the GVC ladder. In the high-tech industry - for instance, the semiconductor industry - the reason for developed countries to preserve more is directly linked to security or political considerations. On this note, this chapter links Taiwan to China, and explains the past changes of Taiwanese investment in China, especially in the IT/electronic industries. The structure of this chapter is as follows: the first part is the definition of GVC theory, whilst the second part explains the importance of IT/electronic industry, and the implication of IT industry in relation to national security. The third part focuses on the importance of the IT industry in Taiwan and provides a brief history of Taiwanese investment in China. The fourth part is composed of three sections, USA-Taiwan technology connections, Taiwan-China technology connections, and finally USA-Taiwan-China connections. The fifth part explores the impacts of Taiwanese manufacturers in China on the Chinese IT/electronic industry, using Foxconn as a case study, and, finally, I conclude that Taiwanese IT/electronic industries will have to face fierce competition with domestic Chinese entrepreneurs.